Sexual Orientation Modulates Endocrine Stress Reactivity - Juster, Robert-Paul; Hatzenbuehler, Mark L.; Mendrek, Adrianna; Pfaus, James G.; Smith, Nathan Grant; Johnson, Philip Jai; Lefebvre-Louis, Jean-Philippe; Raymond, Catherine; Marin, Marie-France; Pruessner, Jens C. (My University, 2015)
Background
Biological sex differences and sociocultural gender diversity influence endocrine stress reactivity. Although numerous studies have shown that men typically activate stronger stress responses than women when exposed to laboratory-based psychosocial stressors, it is unclear whether sexual orientation further modulates stress reactivity. Given that lesbian, gay, and bisexual (LGB) individuals frequently report heightened distress secondary to stigma-related stressors, we investigated whether cortisol stress reactivity differs between LGB individuals and heterosexual individuals in response to a well-validated psychosocial stressor.
Methods
The study population comprised 87 healthy adults (mean age, 25 years) who were grouped according to their biological sex and their gendered sexual orientation: lesbian/bisexual women (n = 20), heterosexual women (n = 21), gay/bisexual men (n = 26), and heterosexual men (n = 20). Investigators collected 10 salivary cortisol samples throughout a 2-hour afternoon visit involving exposure to the Trier Social Stress Test modified to maximize between-sex differences.
Results
Relative to heterosexual women, lesbian/bisexual women showed higher cortisol stress reactivity 40 min after exposure to the stressor. In contrast, gay/bisexual men displayed lower overall cortisol concentrations throughout testing compared with heterosexual men. Main findings were significant while adjusting for sex hormones (estradiol-to-progesterone ratio in women and testosterone in men), age, self-esteem, and disclosure status (whether LGB participants had completed their “coming out”).
Conclusions
Our results provide novel evidence for gender-based modulation of cortisol stress reactivity based on sexual orientation that goes beyond well-established between-sex differences. This study raises several important avenues for future research related to the physiologic functioning of LGB populations and gender diversity more broadly.
Keywords: Cortisol; Gender diversity; Sex differences; Sexual orientation; Stress reactivity; Trier Social Stress Test; 150